Cayley graphs of gyrogroups - Limpapat Bussaban (2019)
© 2019, Institute of Mathematics, Academy of Sciences Moldova. All rights reserved. Gyrogroup is a generalization of group. It is well-known that any group can be viewed as a gyrogroup with trivial gyroautomorphism. In this article, the Cayley graphs of gyrogroups are discussed and some well-known properties in Cayley graphs of groups will be proved for Cayley graphs of gyrogroups.